(untitled) (Journal of Environmental Microbiology and Toxicology, 2018)
Acetylcholinesterase (AChE) is recognised as the key enzyme in the nerve signal system. It terminates nerve impulses by catalysing the hydrolysis of the neurotransmitter acetylcholine. Acetylcholinesterase is a unique molecular aim of a target for insecticides such as organophosphate (OP) and carbamate (CB) pesticides. Recent studies have recognized acetylcholinesterase activity and its inhibition as a useful human’s and animal’s biological indicator of toxicant poisoning. Fish may not be directly exposed by insecticide since this insecticide is created to kill pest which eventually affecting the crops. But when insecticide applied to crops or directly to the soil, it can be absorbed by the soil and affect nearest water bodies through the rain. This is how insecticide can contaminate the water resources thus affecting aquatic organisms especially the fish. Many insecticides such as organophosphates are highly toxic to aquatic organisms. Measurement of toxicant by using AChE inhibition has been widely used in toxicity studies, a biosensor or as a bioindicator having an effect on the nervous system of aquatic animals following exposure to pesticides or any other toxicants present in the environment especially in water bodies. The aim of this review is to discuss the latest study of in vitro assay of acetylcholinesterase for the detection of insecticide, the relation of insecticide contamination to the aquatic environment including its effect on aquatic life especially the fish.